Labour's Call from behind the 'Iron Curtain' : bulletin of the Socialist Union of Central-Eastern Europe. (London, 1960)
Bibliotheek Camille Huysmans
Engels
Periodiek
Keywords: Socialistische Internationale; socialistische pers; Oost-Europa.